2022
DOI: 10.14233/ajchem.2022.23981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Molecular Modeling of Pyrazole-Phthalazine Hybrid Derivatives Bearing 2-Aryloxy Quinoline Nucleus and their Computational Quantum Mechanical Modelling

Abstract: In present work, the synthesis, characterization, antibacterial and anticancer activities of a novel series of 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives bearing 2-aryloxyquinoline nucleus (6a-l) is reported. In vitro antibacterial and anticancer activities against used strains and two cell lines A549 and HepG2 as well as enzyme inhibitory activities against EGFR and FabH were carried out. The most potent inhibitory activity against EGFR was displayed by compound 6l and against FabH by compound 6i. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Based on the potential planarity of the optimized compound, two main cores of atoms 7a-h were found, so that two imaginary planes were passed through atoms, where the first plane was passed from imidazole ring having R1 substitution and the second plane was passed from benzochromene core having R2 substitution, therefore in compounds 7a-h there is only one twist angle θ. It was conventional that the smaller the molecular orbital energy gap ∆E, the greater the reactivity and lower kinetic stability of the materials, but from recent work we know that this conventional relation is not obeyed in all the cases [27][28][29]. The factors calculated from the quantum computational DFT study of all the compounds 7a-h are shown in Table -5.…”
Section: Computational Studiesmentioning
confidence: 99%
“…Based on the potential planarity of the optimized compound, two main cores of atoms 7a-h were found, so that two imaginary planes were passed through atoms, where the first plane was passed from imidazole ring having R1 substitution and the second plane was passed from benzochromene core having R2 substitution, therefore in compounds 7a-h there is only one twist angle θ. It was conventional that the smaller the molecular orbital energy gap ∆E, the greater the reactivity and lower kinetic stability of the materials, but from recent work we know that this conventional relation is not obeyed in all the cases [27][28][29]. The factors calculated from the quantum computational DFT study of all the compounds 7a-h are shown in Table -5.…”
Section: Computational Studiesmentioning
confidence: 99%